Investigation of correlation of generated nuclearactive particles in the protonantiproton annihilation at momenta 22.4 and 32 GeV / c - Boos, E. G.; Izbasarov, M.; Pokrovsky, N. S.; Samoilov, V. V.; Temiraliev, T.; Tursunov, R. A.; Zhautykov, B. O. (21st International Symposium on Heavy Ion Inertial Fusion. Autonomous Organization of Education “Nazarbayev University”, 2016)
Separation of the individual events corresponding to antiproton-proton annihilation gives the possibility to carry out the analysis of multiparticle correlations for generated particles and to compare them with corresponding data for inelastic pp and non-annihilation p̃p interactions...
Keywords: nuclearactive particles; proton-antiproton; Research Subject Categories::NATURAL SCIENCES::Physics::Elementary particle physics